The American Psychiatric Publishing textbook of psychiatry - Hales, Robert E.; Roberts, Laura Weiss , 1960-; Yudofsky, Stuart C. (American Psychiatric Publishing, 2014)
The new sixth edition -- the only comprehensive psychiatry textbook to integrate all the new DSM-5(R) criteria -- provides the most up-to-date, authoritative, insightful foundational text in the field. Its contributors include authors of the definitive texts in their areas of specialization.